Bifunctional nanoarrays for probing the immune response at the single-molecule level. - Cai, H; Depoil, D; Palma, M; Sheetz, M; Dustin, M; Wind, S (2013)
Bifunctional nanoarrays were created to simulate the immunological synapse and probe the T-cell immune response at the single-molecule level. Sub-5 nm AuPd nanodot arrays were fabricated using both e-beam and nanoimprint lithography. The nanoarrays were then functionalized by two costimulatory molecules: antibody UCHT1 Fab, which binds to the T-cell receptor (TCR) and activates the immune response, bound to metallic nanodots; and intercellular adhesion molecule-1, which enhances cell adhesion, on the surrounding area. Initial T-cell experiments show successful attachment and activation on the bifunctional nanoarrays. This nanoscale platform for single-molecule control of TCR in living T-cells provides a new approach to explore how its geometric arrangement affects T-cell activation and behavior, with potential applications in immunotherapy. This platform also serves as a general model for single-molecule nanoarrays where more than one molecular species is required.